2023
DOI: 10.1007/s00376-023-2379-0
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Atmospheric Chemistry Research in China: Establishing a Theoretical Framework for the “Air Pollution Complex”

Abstract: Atmospheric chemistry research has been growing rapidly in China in the last 25 years since the concept of the “air pollution complex” was first proposed by Professor Xiaoyan TANG in 1997. For papers published in 2021 on air pollution (only papers included in the Web of Science Core Collection database were considered), more than 24 000 papers were authored or co-authored by scientists working in China. In this paper, we review a limited number of representative and significant studies on atmospheric chemistry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 184 publications
0
13
0
Order By: Relevance
“…Table 1 indicates that the BC mass concentration was 22.4-4667.5 ng m À3 in Etuoke Banner, with an average value of 456.6 ng m À3 , accounting for 2.20% of the mass fraction of PM 2.5 . The BC mass concentration in Etuoke Banner is much lower than that in Beijing (Liu et al, 2018), Nanjing (Shen, Wang, Kong, Zhang, et al, 2021), Guangzhou (Lin et al, 2019), Wuhan (Zheng et al, 2022), and Chengdu (Yuan et al, 2022), and even lower than that in Litang on the eastern Qinghai-Tibet Plateau (Wang, Liu, et al, 2023). BC liquid , as the main component of BC, has an average value of 361.7 ng m À3 in Etuoke Banner, approximately 79.2% of BC.…”
Section: Observation Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 indicates that the BC mass concentration was 22.4-4667.5 ng m À3 in Etuoke Banner, with an average value of 456.6 ng m À3 , accounting for 2.20% of the mass fraction of PM 2.5 . The BC mass concentration in Etuoke Banner is much lower than that in Beijing (Liu et al, 2018), Nanjing (Shen, Wang, Kong, Zhang, et al, 2021), Guangzhou (Lin et al, 2019), Wuhan (Zheng et al, 2022), and Chengdu (Yuan et al, 2022), and even lower than that in Litang on the eastern Qinghai-Tibet Plateau (Wang, Liu, et al, 2023). BC liquid , as the main component of BC, has an average value of 361.7 ng m À3 in Etuoke Banner, approximately 79.2% of BC.…”
Section: Observation Overviewmentioning
confidence: 99%
“…In China, numerous in-depth studies on the characteristics of BC pollution have been carried out in dense urban agglomeration areas such as the North China Plain (NCP) region, the Yangtze River Delta (YRD) region, the Pearl River Delta (PRD) region, the Twain-Hu Basin, and the Sichuan Basin (Chen, Zhao, et al, 2023;Lin et al, 2019;Pei et al, 2022;Wan et al, 2023;Wei et al, 2023;Yang et al, 2022;Yuan et al, 2022;Zhang et al, 2023;Zheng et al, 2022). Yang et al (2022) found that the refractory BC (rBC) core mass size distribution was bimodal, with a small secondary mode at $687 nm in NCP.…”
mentioning
confidence: 99%
“…Fine particulate matters (PM 2.5 ) is the primary contributor to severe haze events in urban areas in China, with profound implications for global climate, social economy, and public health. The current National Ambient Air Quality Standards in China set the annual average PM 2.5 level to be below 35 μg/m 3 , a standard much higher than the 5 μg/m 3 value recommended by the World Health Organization. , Despite a significant reduction in SO 2 emissions in China, taking Beijing as an example, with annual average SO 2 concentrations decreased by 82% from 22 ppb in 2013 to 4 ppb in 2018, sulfate concentrations experienced a more modest decline of 37%, falling from 19.1 μg/m 3 in 2013 to 12.1 μg/m 3 in 2018 . The noted discrepancy, also observed in other regions globally and particularly pronounced during wintertime, presents a formidable challenge for air pollution control in China and worldwide …”
Section: Introductionmentioning
confidence: 99%
“…The complex air pollution in China is characterized by high concentrations of particulate matter and gas pollutants such as NOx, NH 3 , and VOCs. 79 In particular, primary and secondary particles with high concentrations provide a huge reaction interface for multiphase and heterogeneous reactions. The enormous, highly reactive surface of atmospheric particulate matter significantly enhances the oxidizing capacity, which causes the explosive transformation of gaseous pollutants to particulate matter and reduces the atmospheric environmental capacity for primary emissions.…”
mentioning
confidence: 99%
“…The complex air pollution in China is characterized by high concentrations of particulate matter and gas pollutants such as NOx, NH 3 , and VOCs . In particular, primary and secondary particles with high concentrations provide a huge reaction interface for multiphase and heterogeneous reactions.…”
mentioning
confidence: 99%